Bauran Marketing Jasa Pendidikan Sekolah Dasar Muhammadiyah - S, Sutama; Sri Walji Hasthanti (Universitas Muhammadiyah Surakarta, 2019)
This study aims to describe the marketing mix of educational services at Muhammadiyah Plus Elementary School in Salatiga City which consists of products,prices, locations, promotions, human resources, physical evidence, and the learningprocess. This research was conducted using qualitative methods. Data is obtainedfrom the results of interviews directly to the speakers, environmental observationsthat support research, study documentation. This study uses a flow analysis model.Marketing education services are promotional activities regarding products, prices,locations, physical evidence / school infrastructure, and the process of schoolactivities carried out by people / human resources.